الجرائم العنصرية وخطاب الكراهية في وسائل التواصل االجتماعي - نور الهدى طبة; وئام بن لوصيف (My University, 2026)
Summary: Racist crimes and hate speech on social media platforms represent one of the most dangerous challenges arising from contemporary digital evolution. These phenomena involve broadcasting and disseminating content that carries discriminatory or inciting characteristics directed against individuals or groups based on race, religion, color, origin, or other bases of identity. This undermines the principle of equality among individuals and erodes values of tolerance and coexistence within society. The danger of this phenomenon intensifies in the digital environment due to the distinctive features of social media, particularly the extraordinary speed of information circulation, its vast scope of dissemination without geographical restrictions, the possibility of concealing the perpetrator's identity, and the weakness of preemptive content moderation on many platforms. This renders these platforms fertile ground for the proliferation and rapid evolution of hate speech. Consequently, the impacts of these practices extend beyond the targeted individuals to encompass society as a whole, by threatening social stability, stirring tensions and divisions. This necessitates activating legal and technical mechanisms to confront them and curb their spread
Keywords: Keywords: Hate crimes based on race; Hate speech; Social media; Racial discrimination; Incitement; Digital development; Digital environment.; الكلمات المفتاحية: جرائم عنصرية، خطاب الكراهية، وسائل التواصل الاجتماعي، تمييز عنصري، تحريض، تطور رقمي، بيئة رقمية.